Benefits of a near-peer program from the tutors’ perspective: a survey of Australian junior doctors in a regional teaching program - David Medveczky; Alicia Mitchell; Eleonora Leopardi; Amanda Dawson (BMC Medical Education)
Abstract Background Near-peer teaching has been shown to provide diverse benefits for both tutees and tutors in senior medical student and junior trainee settings. However, junior trainees may face more obstacles in teaching including competing clinical priorities and time management. We sought to investigate the challenges and benefits of engaging in near-peer teaching for junior trainees within our local context. Our Near-Peer Medical Teaching (NPMT) teaching program is designed and facilitated by junior doctors for medical students at the Central Coast Clinical School (University of Newcastle) of the Joint Medical Program. Methods Current and past NPMT tutors participated in an online survey from October 2022 to April 2023. Tutors were asked about feasibility of teaching within a work environment, perceived benefits from their experience and attitudes towards medical education. Results Teaching experience appears to be influenced by competing clinical priorities and convenience of session times, but it does not appear to exert considerable stress on tutors likely due to self-selection of tutors with prior enjoyable teaching experience. Furthermore, this study indicates that junior doctors derived enjoyment and developed clinical skills and professional qualities, which are important factors in increasing job satisfaction and ameliorating burn-out in this cohort. Conclusions Junior doctors appear to benefit from engaging in near-peer programs in the Australian teaching hospital setting. Further research should include qualitative methodologies to explore the perspectives of Australian junior doctors’ more deeply.